Temperature-Dependent Elongation Sensitivity of a Silica Singlemode–Multimode–Singlemode Optical Fiber Sensor at 1310 nm - Yofinda Eka Setiawan; Aslam Chitami Priawan Siregar; Allif Rosyidy Hilmi; Aprilia Dewi Ardiyanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The elongation sensor based on the singlemode–multimode–singlemode (SMS) optical fiber structure is an interesting candidate for strain measurement applications, as its optical response is quite sensitive to light propagation changes in the multimode section. Even so, temperature's influence should not be overlooked, as it affects the sensor's response and is a parameter that warrants serious consideration during calibration. Based on this, the study examined the extent to which temperature affects the elongation sensitivity of a silica-based SMS optical fiber sensor, using a 5.4 cm multimode segment tested at a wavelength of 1310 nm. Testing covered three temperature variations (38, 48, and 58 °C), with elongation applied gradually from 0 to 100 µm in 10 µm increments, and each point was repeated 3 times to evaluate short-term repeatability. Changes in optical loss (dB) were used as the main indicator of the sensor's response. The results showed a fairly consistent pattern, optical loss tended to increase with elongation across all three tested temperatures. The linear regression results showed a sensitivity of 0.002388 dB/µm at 38 °C, increasing to 0.002723 dB/µm at 48 °C and reaching 0.003062 dB/µm at 58 °C. The respective R² values were 0.9378, 0.9273, and 0.9346. These values confirming a near-linear relationship between optical loss and elongation within this testing range. When the temperature was raised from 38 to 58 °C, the sensitivity increased approximately 28%. The relatively small standard deviation further supports the sensor's fairly good repeatability. Overall, these results indicate that temperature needs to be incorporated into the calibration process of SMS elongation sensors. However, these findings remain preliminary and apply specifically to the tested configuration, namely a 5.4 cm MMF segment at 1310 nm, within a temperature range of 38–58 °C and elongation of 0–100 µm. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production